ENHANCING GLOBAL RISKS IN THE WORLD POLITICAL SPACE - Наумкіна, С. М.; Білоусов, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
There of is political potential of catastrophes in society of risk. Exposure of risk level in society of it can solve problem by creation of the correct communicative field, in that a dialogue comes true between different conceptions and risk estimations that exist in society. However, of along from them there is a danger of origin of «communication risk». Due of to a world wide web risks are implanted in fabric of other social organisms, mutually pass to each other. As of a result there are взаємообумовлені changes, common «fascination» by a risk. The of theoretical versions of of «society of risk» of were substantially complemented after the acts of terrorism on of September, 11, 2001, that marked not only the end of of «period after cold war», but also beginning of possible death of all system of western democracy. Social and national safety of citizens, appeared in the direction, related to globalization, that converts and modifies on our eyes not only the terms of social life of man but also risk factors. The calls of risk become the calls of democracy, to civil society, legal state and human rights. Civil society found oneself, thus, under the breech-sight of two forces – the state that wants what then did not guard to get the former power and force, and network structures of violence, that proclaimed war against the values of individual freedom, civil society and state. A risk theme lies not in industry of the subject measuring, but consists of the state of sentinel and social measuring. The production of risks is inherent to all public spheres: economic, political, social. A risk becomes the growing component of public production. The concentration of risks results in a «effect to the boomerang», id est to omnifying and globalizations of risks, that violate class and national limits. A «effect to the boomerang» generates a feed-back, and a consumption of risk simultaneously is beginning of his production. Consequently, as risks are predefined by probabilistic character of many natural, social and technological processes, a number of the casual objective and subjective factors not forecast, influences on development of that, then it predetermines impossibility of management society as by the hardly determined system, that is confirmed by all socio-political development of humanity.